Dielectric investigation of the liquid crystal compound with the directSmA*–SmCA* phase transition. Issue 5 (8th April 2016) - Perkowski, P.; Mrukiewicz, M.; Herman, J.; Kula, P.; Jaroszewicz, L.
ABSTRACT: New compound showing a direct SmA*–SmCA * phase transition was synthesised. As far as authors know there are a few pure compounds showing para- and antiferroelectric phases without SmC* between them. Direct current (DC) field applied into a planar-oriented cell induces ferroelectric SmC* phase in an investigated compound. Typical for SmC*, Goldstone mode starts to be detectable. DC field also shifts down the temperature of a SmCA * phase creation. Moreover, modes in the appearing antiferroelectic phase are enhanced by DC field. This paper shows and discusses relations between modes detected in SmA*, SmCA * and SmC* (SmC* phase – nucleated by DC field) phases. Parameters of observed modes are calculated using the Cole–Cole relaxation model and a calculation procedure useful especially for high frequency relaxations (higher than 200 kHz). GRAPHICAL ABSTRACT: